Factores maternos y practicas de estimulación intrauterina en adolescentes embarazadas Hospital Leoncio Prado Huamachuco 2011 - Cruz Alonso, Doris Teresa (2011)
The present investigation of descriptive type, correlacional of transverse court, was realized by pregnant teenagers that they were present at his prenatal control during the months October, 2010 - April, 2011 in the hospital Leoncio meadow Huamachuco, with the purpose of determining the relation that exists between the mother factors: age, degree of instruction, occupation, marital status, origin and the practices of intrauterine stimulation in pregnant teenagers. The sample universe was constituted by 54 pregnant teenagers selected according to criteria of incorporation established. For the compilation of information I apply a survey to him on Practices of intrauterine stimulation (EPEIAE), which consists of twelve articles. The obtained information was tabulated and presented in tables. For the analysis there was in use the test of independence of criterion chi square (X2). Of the discussion of the results the following conclusions were obtained: 74.0 per cent of pregnant teenagers they have between 17 and 19 years, degree of primary instruction 51.9 per cent, 74.0 per cent they were housewives, cohabitants 77.8 per cent and they come from Huamachuco's city 68.5 per cent; likewise 72.2 per cent of the pregnant teenagers they realize bad practices of intrauterine stimulation. The age of the teenagers has significant relation and the degree of instruction highly significant relation with the practices of intrauterine stimulation. The occupation, marital status and origin of the pregnant teenagers did not have significant relation with the practices of intrauterine stimulation.